Gestión de cobranza y su influencia en rentabilidad de la Caja de Ahorros y Créditos Piura sede Nueva Cajamarca, 2021 - Fernandez Pasancho, Anderson (2022)
The general objective of this research was to determine the degree of relationship between the collection management and the profitability of the Caja de Ahorros y Crédito Piura headquarters Nueva Cajamarca, 2021, opting for an applied research and non-experimental design, of which it was included as a sample of 34 workers of said institution, those who were surveyed by means of a questionnaire, since it was concluded that the collection management is very efficient. On the other hand, its profitability, since in the gross profit margin it obtained an increase of 0.16; on the other hand, in the operating profit margin it gave 0.076; likewise, the return on assets had an increase of 6.8; finally, return on capital had 6.8. Finally, there is a relationship between the collection management and the profitability of said institution, approved significance of 0.000 and a correlation of rs=0.591 which is positive and medium; At the same time, collection policies maintain a considerable positive relationship (sr=0.766; p=0.000); collection strategies maintain a weak positive relationship (sr=0.467; p=0.005); the collection system maintains a very weak positive relationship (sr=0.155; p=0.380), however, the administration of the collection personnel (sr=0.008; p=0.964) does not maintain a relationship with the profitability of the company.